Relationship pathways : from adolescence to young adulthood - Laursen, Brett Paul.; Collins, W. Andrew, 1944- (Thousand Oaks : Sage Publications, Inc, 2012)
'Research on adolescent relationships has rapidly expanded during the past decade. Keeping apace with research advances is a difficult challenge. Harder still is integrating the literature into a coherent whole. This volume is designed to guide the reader through the research on close relationships before, during, and after adolescence. We are fortunate that some of the world's foremost experts on adolescent relationships agreed to summarize what is known in their respective fields of expertise. The volume begins with a section on developmental pathways and processes. This section defines relationships processes and describes individual and contextual factors that influence them. The next section is devoted to family relationships. Separate chapters are devoted to sibling relationships and parent-child relationships during the transition into adolescence and during the transition into young adulthood. The final two sections concern peer relationships'--
Includes bibliographical references and indexes.
Keywords: Adolescence; Adolescent psychology; Teenagers -- Family relationships; Teenagers -- Sexual behavior; Interpersonal relations